Juridical Analysis of Default Disputes in Online Loan Agreements under the Indonesian Civil Code - Febriana, Asyri; Utary, Baiq Ishariaty Wika; Idrus, Nabain (Sekolah Tinggi Ilmu Kepolisian, 2026)
The development of electronic transactions has created ambiguity in the mechanisms for resolving disputes arising from breaches of contract (wanprestasi) in online lending agreements. This study aims to analyse the juridical basis for resolving breach of contract disputes based on the Civil Code (KUHPerdata). The method used is normative juridical, with a statutory and literature approach. The results of the study indicate that online agreements remain valid under Article 1320 of the Civil Code and possess binding legal force; therefore, breaches of contract can be legally enforced. However, the digital nature of online lending agreements presents its own challenges, particularly in terms of dispute resolution mechanisms. The novelty of this research lies in analysing the relationship between the characteristics of electronic agreements and the models of dispute resolution for breach of contract. This study contributes by providing a more specific juridical framework as a basis for the development of practices and policies in resolving disputes arising from online agreements.